2006
DOI: 10.1111/j.1524-475x.2006.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the treatment of venous ulcers

Abstract: An advisory panel of academicians, private practice physicians, podiatrists, nurse clinicians, research nurses, industrial scientists, and an epidemiologist was chosen to develop guidelines for the treatment of venous ulcers of the lower extremity. METHODSPrevious guidelines, meta-analyses, PubMed, MEDLINE, EMBASE, The Cochrane Database of Systematic Reviews, recent review articles of venous ulcer treatment, and the Medicare/CMS consensus of usual treatment of chronic wounds were all reviewed for evidence. Gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
145
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(151 citation statements)
references
References 150 publications
2
145
0
4
Order By: Relevance
“…Os guidelines (22) de tratamento de úlcera varicosa recomendam o uso de cobertura tópica associada à terapia de compressão. Existem várias coberturas e a avaliação do aspecto da ferida, tamanho, tipo de tecido e exsudato, devem ser considerados para a escolha da mais adequada.…”
Section: Discussionunclassified
“…Os guidelines (22) de tratamento de úlcera varicosa recomendam o uso de cobertura tópica associada à terapia de compressão. Existem várias coberturas e a avaliação do aspecto da ferida, tamanho, tipo de tecido e exsudato, devem ser considerados para a escolha da mais adequada.…”
Section: Discussionunclassified
“…It is indicated in the treatment for infected wounds and ulcers, impetigo and to eradicate MRSA in the nostrils 36 . The topic use of mupirocin for the decontamination of venous ulcers has not been described 35,39 nor is it recommended according to a systematic review about the topical indication of this antimicrobial 38 . On the venous ulcer treatment guidelines, the use of topical antibacterial agents can be necessary to reduce the microbial load, but this document does not indicate the class type of the agent 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The topic use of mupirocin for the decontamination of venous ulcers has not been described 35,39 nor is it recommended according to a systematic review about the topical indication of this antimicrobial 38 . On the venous ulcer treatment guidelines, the use of topical antibacterial agents can be necessary to reduce the microbial load, but this document does not indicate the class type of the agent 39 . A study conducted in Brazil found 38% of MRCoNS isolates, and multi-drug resistance was detected in 86%; however, the MLS B i phenotype was not investigated 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional and gold standard therapy is application of the multilayered compression dressing. This aims to improve the venous return by passive promotion of the peripheral hemodynamic pump (calf and the foot muscles) [6]. However, such routine practice is not necessarily applicable to large, longstanding and bilateral leg ulcers in obese and minimally mobile patients.…”
Section: • Pyoderma Gangrenosummentioning
confidence: 99%